Cross-cultural adaptation and validation of the Global Physical Activity Questionnaire among healthy Hungarian adults - Pongrác Ács; József Betlehem; András Oláh; Barbara Bergier; Kata Morvay-Sey; Alexandra Makai; Viktória Prémusz (BMC, 2020)
Abstract Background Physical activity (PA) is an important factor among the determinants of health due to it's protective factor and preventive role. Self-reported measures such as questionnaires are most commonly used in public health studies, but may over- or underestimate actual patterns of PA. Therefore, accelerometers are widely used to assess concurrent validity. The aim of the present study was to adapt and validate the self-administered GPAQ - Hungarian version (GPAQ-H) against accelerometer data and IPAQ-Hungarian long version (IPAQ-HL) in Hungarian healthy young adults. Methods A cross-sectional comparative study was conducted to examine the last 7 days PA by GPAQ-H, comparing with IPAQ-HL and Actigraph GT3X accelerometer to measure concurrent validity and reliability. A convenient sample of 300 young adults was recruited in January - July 2018 at the University of Pécs, in South-Hungary, 120 participants (age 21.53 ± 1.75 years, 46.66% male) were included in the validity and reliability study. Results Significant differences between the three instruments were found (p < 0.001) in all scores, except PAQs vigorous activities (p = 0.332) and GPAQ-H and accelerometer MVPA score (p = 0.424). A moderate KMO measure was found (0.538) with a significant Barlett's test of Sphericity (279.51; p < 0.001). The total variance was explained as 81.10%. The reliability of the GPAQ-H instrument with all domain's scores was 0.521 (CI 0.371-0.644). We found in all intensity scores and sitting time good reliability scores (R = 0.899-987, p < 0.001) between the baseline and follow-up (N = 33 random subsample). The Bland-Altman plots were showed that GPAQ-H overestimates vigorous activities by 212.75 min/week (331.82-757.42) and MVPA by 104.93 min/week (− 1016.98-807.11). A high difference, 6336.79 min/week (CI 3638.18-9035.40) was revealed regarding sitting, as GPAQ-H largely underestimated the time spent sedentary. Conclusions The Hungarian GPAQ self-administered form showed fair to moderate validity with correlation coefficients similar to other European studies. Based on our study's results it could be claimed that the GPAQ-H measurement tool is a valid and reliable questionnaire to measure the healthy Hungarian population's physical activity patterns. However, our results also proved that GPAQ-H alone is not a valid and reliable questionnaire to measure sitting time.